2020
DOI: 10.1111/1749-4877.12435
|View full text |Cite
|
Sign up to set email alerts
|

An initial coprological survey of parasitic fauna in the wild Amur leopard (Panthera pardus orientalis)

Abstract: The Amur leopard, one of nine recently recognized subspecies of leopard, is still the most threatened by a stochastic procession of extinction. Evaluation of the potential danger to the conservation of the Amur leopard originating from disease urgently needs to be studied. Unfortunately, research on the potential risk to Amur leopards caused by disease is rare. In terms of parasitic diseases that affect this species, even basic data for parasitic fauna are absent. The aim of this study is to acquire this knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…A careful analysis [10] of the literature cited in [9] has indicated that this is not the case, because none of these papers contained definite evidence (Table 2). Records in wild felids from South America [50] and other reports [44,46,47,49] are also questionable (Table 2). Nonetheless, recent morphological and genetic data have shown the unequivocal capability of A. abstrusus to infect wild felids.…”
Section: Aelurostrongylus Abstrusus and Wild Felidsmentioning
confidence: 94%
“…A careful analysis [10] of the literature cited in [9] has indicated that this is not the case, because none of these papers contained definite evidence (Table 2). Records in wild felids from South America [50] and other reports [44,46,47,49] are also questionable (Table 2). Nonetheless, recent morphological and genetic data have shown the unequivocal capability of A. abstrusus to infect wild felids.…”
Section: Aelurostrongylus Abstrusus and Wild Felidsmentioning
confidence: 94%
“…For studies at the population-level or disease surveillance, fresh faeces can be collected directly from the habitat (e.g., from pastures, dwellings, latrines, or under nesting sites, depending on the species) without any direct contact with the animal (wild cats Felis silvestris silvestris [86]; badgers Meles meles [87]; Gentoo penguins Pygoscelis papua [88]; several Carnivora and Artiodactyla species in Brazil [89]; Amur leopards Panthera pardus orientalis [90]; wolverines Gulo gulo [42]). In the case of large mammals, GPS-telemetry might be useful to monitor animal movements and locate areas where faeces are most likely to be found, as it was conducted by Van der Goot and colleagues [77] on southern white rhinoceros or by Di Francesco and colleagues [91] on wolf (Canis lupus) packs.…”
Section: Faecesmentioning
confidence: 99%
“…Since Amur tiger (Panthera tigris altaica) are wandering across the Sino-Russia border areas, it has attracted considerable attention as monitoring, protecting, and saving this endangered rare big predator and their prey species are popular topics of interest (Hou et al 2020;Qi et al 2021Qi et al , 2022Wang et al 2021). In this study, we used UAV and infrared cameras as video acquisition equipment, and infrared thermal pictures of Amur tigers and their main prey, such as sika deer (Cervus nippon), roe deer (Capreolus pygargus), reindeer (Rangifer tarandus), and red deer (Cervus elaphus) (Gu et al 2018), as the research objects.…”
Section: Introductionmentioning
confidence: 99%
“…Since Amur tiger ( Panthera tigris altaica ) are wandering across the Sino‐Russia border areas, it has attracted considerable attention as monitoring, protecting, and saving this endangered rare big predator and their prey species are popular topics of interest (Hou et al. 2020; Qi et al. 2021, 2022; Wang et al.…”
Section: Introductionmentioning
confidence: 99%